Neuromuscular function, hormonal, and mood responses to a professional rugby union match - West, D. J.; Finn, C. V.; Cunningham, D. J.; Shearer, D. A.; Jones, M. R.; Harrington, B. J.; Crewther, B. T.; Cook, C. J.; Kilduff, L. P. (The Journal of Strength and Conditioning Research, 2014)
We examined the recovery time-course of neuromuscular function (NMF), the testosterone and cortisol hormonal milieu, and mood for 60 hours after a competitive match in professional rugby union players (n = 14). Thirty-six hours prematch (19:30 hours kick-off), baseline saliva samples (testosterone, cortisol, and testosterone to cortisol [T/C] ratio), countermovement jump performances (peak power output [PPO]), and mood disruption (Brief Assessment of Mood Questionnaire) were collected and was repeated at 12, 36, and 60 hours postmatch. Peak power output decreased below baseline at 12 hours (baseline 6,100 ± 565 W vs. 12 h 5,680 ± 589 W; p = 0.004) and 36 hours (5,761 ± 639 W; p < 0.001) but had recovered at 60 hours (5,950 ± 505 W; p = 0.151). Cortisol concentrations increased from baseline at 12 hours (baseline 0.40 ± 0.09 µg/dl vs. 12 h 0.60 ± 0.20 µg/dl; p = 0.004) and 36 hours (0.60 ± 0.20 µg/dl; p = 0.027) but were similar at 60 hours postmatch. Testosterone concentrations decreased from baseline at 12 hours (baseline 214 ± 84 pg/ml vs. 12 h 151 ± 56 pg/ml; p = 0.023) and 36 hours (173 ± 71 pg/ml; p = 0.016) but were similar at 60 hours postmatch. The T/C ratio decreased from baseline at 12 hours (baseline 551 ± 219 vs. 12 h 266 ± 123; p = 0.001) and 36 hours (310 ± 148; p = 0.027) before returning to baseline at 60 hours postmatch. Mood disturbance increased at 12 hours (p = 0.031) before returning to baseline at 36 and 60 hours postmatch. There were no relationships between changes in PPO, testosterone, cortisol, T/C ratio, and mood. In conclusion, postmatch changes in NMF, salivary hormones, and mood disturbance were identified in professional rugby union players. Players and coaches can expect reduced NMF and hormonal disruption for 36 hours before recovering at 60 hours postmatch, with mood recovered by 36 hours postmatch. Knowledge of these recovery time-courses may prove useful for player training program design and postmatch recovery strategies.